Mixue's business development strategy in South Tangerang through SWOT analysis - I Gede Marendra; I Made Aryata (Law and Economics, 2025)
The culinary business (Food and Beverage) is a business that puts food or beverages as the core of its products. Mixue is one of the franchise companies that currently, Mixue itself offers product ice cream combined with tea drinks. The current culinary business competition requires Mixue to be able to innovate business strategies to be able to present products that meet customer needs. SWOT analysis is a method used to identify business strategy by looking at the Company's internal aspects as well as the Company's external aspects. By using SWOT Analysis, it is known that the Mixue Business is in Quadrant I with the strategy used is aggressive growth (growth oriented strategy). Through the Growth Oriented Strategy, strategies that can be carried out by the Company can be identified, including: 1) Conducting Market Penetration through product bundling of product variants currently owned by Mixue as well as new product variants that are in accordance with Mixue's target market. 2) Conducting Market Development through Mixue's collaboration with Schools, Universities, Airports, Stations and other public facilities that are the target market of Mixue products. 3) Conducting Product Development through the development of Gelato variants and also ice cream products that do not melt easily. 4) Diversification through the development of new products such as snacks or variants of drinking coffee that can be combined with mixue ice cream products.